Regular expression pocket reference - Stubblebine, Tony (O'Reilly, 2003)
Regular expressions are such a powerful tool for manipulating text and data that anyone who uses a computer can benefit from them. Composed of a mixture of symbols and text, regular expressions can be an outlet for creativity, for brilliant programming, and for the elegant solution. While a command of regular expressions is an invaluable skill, all there is to know about them fills a very large volume, and you don't always have time to thumb through hundreds of pages each time a question arises. The answer is the Regular Expression Pocket Reference. Concise and easy-to-use, this li.